Spatial distribution of display sites of Grey Peacock-pheasant in relation to micro-habitat and predators during the breeding season - Somying Thunhikorn; Matthew J. Grainger; Philip J. K. McGowan; Tommaso Savini (Avian Research, 2018)
Abstract Background The destruction and fragmentation of forest in Southeast Asia is accelerating biodiversity loss, resulting in a range of management and conservation actions. For some species, a detailed understanding of microhabitat selection is critical for this, especially in the breeding season. Methods To understand the factors that explain how specific habitats are used by the Grey Peacock-pheasant (Polyplectron bicalcaratum) in the breeding season, we used camera trapping and microhabitat sampling to assess the microhabitat selection of males. We also looked at their interaction with predators in an area of 1200 m × 1200 m at the Huai Kha Khaeng Wildlife Sanctuary, Thailand, between January and May 2013. Results We show that display scrapes are situated on flatter open areas with small saplings and some vines, typified by low horizontal understory density. We hypothesise that this allows a trade-off between courtship display and the avoidance of predators. Our study showed that the position of Grey Peacock-pheasant display scrapes regularly overlapped with predators within the same microhabitat. We hypothesise that the species’ behavioural responses to temporal variation in predation risk allows them to avoid most predators. Conclusions Particular microhabitats are required for Grey Peacock-pheasant display. They avoid predators at these places by being active when predators are not.